Caracterização de resíduos de poda, amostragem de poluentes advindos de sua queima e eficiência de combustão - Neves, Vanessa Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
As urban pruning waste is almost entirely destined for landfills along with all other wastes, there is an environmental concern with the possible products coming from the contact between them and with the early termination of the life of the landfill due to large spaces occupied by bulky pruning waste. A satisfactory and environmentally acceptable solution for such waste would be the use as a fuel, i.e. for energy purposes. This project, therefore, had as objective to characterize the pruning residue for later use as biomass fuel in direct burning. The chemical characterization of the pruning residues obtained at the Itapeva Experimental Campus (UNESP) was carried out by means of the immediate chemical analysis with the determination of the average moisture content (12.03%), to characterize these characteristics. its direct relation with the calorific value of biomass (PCS); (71.11%), a fraction that expresses the ease of ignition and burning of the fuel and greatly influences the gaseous flow profile in the furnace and the chemical reaction rate, that is, it plays an important role in the initial stages of combustion of biomass; of the ash content (5.71%), which shows the residues coming from the combustion of the organic components and oxidation of the inorganics and can negatively influence the PCS. By calculation, the fixed carbon content (23.18%) was determined, which is the remaining mass after the release of the volatile compounds excluding the ash and the moisture content. In addition to the chemical characterization, it is necessary to characterize the energy of a fuel and, with that, the residues in question were analyzed in calorimeter to obtain the superior calorific value (PCS). The mean value found was 17013 J / g (to the moisture content of approximately 16%). Sequentially, the chemical analysis of the cell wall of the biomass was carried out as extractive content (13.80%), lignin content (36.27%), and holocellulose content...

Como os resíduos de poda urbana são quase em sua totalidade destinados a aterros sanitários, juntamente com todos os outros resíduos, surge a preocupação ambiental com os possíveis produtos advindos do contato entre eles e, também, com o fim precoce da vida útil dos aterros devido aos grandes espaços ocupados pelos resíduos volumosos de poda. Uma solução satisfatória e ambientalmente aceitável para tais resíduos seria a utilização como combustível, ou seja, para fins energéticos. Esse projeto, portanto, teve como objetivo caracterizar o resíduo de poda para posterior utilização como combustível. Para tanto, foi realizada a caracterização química dos resíduos de poda obtidos no Campus Experimental de Itapeva (UNESP) através da análise química imediata, o poder calorífico da biomassa (PCS); do teor de materiais voláteis (71,11%), fração que expressa a facilidade de ignição e queima do combustível e influi muito no perfil de escoamento gasoso no forno e na velocidade química da reação, ou seja, tem papel importante nas etapas iniciais de combustão da biomassa; do teor de cinzas (5,71%), teor que demonstra os resíduos provenientes da combustão dos componentes orgânicos e oxidação dos inorgânicos e podem influenciar negativamente no PCS. Por cálculo determinou-se o teor de carbono fixo (23,18%), que é massa restante após a liberação dos compostos voláteis excluindo as cinzas e o teor de umidade. Além da caracterização química faz-se necessária a caracterização energética de um combustível e, com isso, os resíduos em questão foram analisados em calorímetro para obtenção do poder calorífico superior (PCS). Os resultados mostram que foi de 17013 J/g (para o teor de umidade de aproximadamente 16%). Sequencialmente, realizou-se a análise química da parede celular da biomassa como teor de extrativos (13,80%), teor de lignina (36,27%), teor de holocelulose (49,93%). Devido a essas últimas...
Keywords: Energia - Fontes alternativas; Residuos vegetais; Biomassa - Combustão; Poluentes; Renewable energy sources